2005
DOI: 10.3171/foc.2005.19.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal surgery of the midline skull base: anatomical study and clinical considerations

Abstract: Object The midline skull base is an anatomical area that extends from the anterior limit of the cranial fossa down to the anterior border of the foramen magnum. Resection of lesions involving this area requires a variety of innovative skull base approaches. These include anterior, anterolateral, and posterolateral routes, performed either alone or in combination, and resection via these routes often requires extensive neurovascular manipulation. The goals in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
199
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(206 citation statements)
references
References 63 publications
1
199
2
4
Order By: Relevance
“…This ability has recently been shown to offer a potentially more sensitive appraisal of tumor spread than is available with contrastenhanced MR imaging. 5,30,44 An example of germinoma dissemination noted at the time of endoscopic tumor biopsy is shown in Fig. 2.…”
Section: Advances In Neurosurgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability has recently been shown to offer a potentially more sensitive appraisal of tumor spread than is available with contrastenhanced MR imaging. 5,30,44 An example of germinoma dissemination noted at the time of endoscopic tumor biopsy is shown in Fig. 2.…”
Section: Advances In Neurosurgical Managementmentioning
confidence: 99%
“…The advent of endoscopic-assisted transnasal surgery offers an appealing alternative to intracranial surgery for tumors situated in the parasellar region. 5,16,34 Using the nasal aperture as a primary surgical corridor, the transsphenoidal route or extended cranial-base routes can be used to resect intradural tumors. Currently there is no dedicated study of transnasal endoscopically assisted surgery for parasellar CNS GCT, but the anatomical considerations do not differ greatly from other tumors that have been successfully managed using this approach.…”
Section: Advances In Neurosurgical Managementmentioning
confidence: 99%
“…Cavallo et al reported the lateral limitation of the foramen magnum is the anterior third of the occipital condyle, as the hypoglossal canal is located anterior and in the middle third of each condyle (3)(4). Laterally extended lesions must be treated by additional surgical approaches or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Critical neurovascular structures, primarily the paraclival internal carotid artery (ICA) segments and the lower cranial nerves, are generally considered to represent the lateral limits of safe exposure. 19,21,22 Clinically, clival lesions are often found to displace, invaginate around, and extend beyond these structures, thus restricting the success of an EEEA. 23 Understanding the specific anatomic limitations associated with this approach is important to better predict preoperatively whether an expanded endoscopic, lateral, or anterior "open" procedure would be most effective in safely achieving the greatest amount of tumor removal.…”
Section: Introductionmentioning
confidence: 99%